Understanding metalepsis : the hermeneutics of narrative transgression - Hanebeck, Julian, 1975- (Narratologia., 2017)
"Understanding Metalepsis provides a state-of-the-art overview of the narratological concept of metalepsis and develops new ways of investigating the forms and functions of metaleptic narratives. Informed by a hermeneutic perspective, this study offers not only an account of the complexities that characterize the process of understanding metaleptic phenomena, but also metatheoretical insights into the hermeneutics of narratology"--